Early carbohydrate antigen 125 as a mortality predictor in hospitalized patients with coronavirus disease 2019 - Moreno-Perez, Oscar; Nuñez, Julio; Sandin-Rollan, Miriam; Arrarte, Vicente; Boix, Vicente; Reus, Sergio; Pinargote-Celorio, Hector; Ribes, Isabel; Alfayate, Rocio; Llorca-Santos, Maria Belen; Martinez-Garcia, Maria Angeles; Chico-Sánchez, Pablo; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Carbohydrate antigen 125 (CA125), is an indicator of inflammation, immune response, and impaired cardiac function. The aim was to investigate whether CA125 behaves as a biomarker of severity and poor clinical outcomes in hospitalized patients with COVID-19. Methods. Serum CA125 (Elecsys CA125 II assay-[Roche Diagnostics GmbH]) was measured in stored biobank samples from COVID-19 hospitalized patients between March 01th 2020 to October 17th 2021. Multiple logistic regression models were built to explore the association between CA125 and clinical outcomes (in-hospital all-cause mortality, need for invasive mechanical ventilation (IMV) or non-invasive respiratory support (nonIRS)), estimating odds ratios (OR; 95%CI). The gradient of risk of CA125 was evaluated by fractional polynomials. Results. 691 patients were included, median age of 63 years [50-76], males (57.2%), with high comorbidity. At admission 85.8% had pneumonia. Median CA125 was 10.33 U/mL [7.48-15.50]. In-hospital mortality rate was 7.2%. After adjusting for confounding factors, CA125 ≥15.5 U/mL (75th percentile) showed an increased risk of death (OR 2.85[1.21-6.71]), as age ≥ 65 years, diabetes and immunosuppression. Further, CA125 as a continuous variable was positive and significantly associated with the risk of death after multivariate adjustment. Mean hospital stay of the patients with CA125 ≥15.5 U/mL, was longer than the rest of the study population. Conclusions. CA125 in the first 72 hours of hospital admission seems a useful biomarker of mortality in hospitalized patients with moderate – severe COVID-19. If our findings are confirmed, the wide availability of this biomarker would make easy its widespread implementation in clinical practice.